2002
DOI: 10.1046/j.1365-313x.2002.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis hrl1 mutation reveals novel overlapping roles for salicylic acid, jasmonic acid and ethylene signalling in cell death and defence against pathogens

Abstract: SummaryDefence against pathogens in Arabidopsis is orchestrated by at least three signalling molecules: salicylic acid (SA), jasmonic acid (JA) and ethylene (ET). The hrl1 (hypersensitive response-like lesions 1) mutant of Arabidopsis is characterized by spontaneous necrotic lesions, accumulation of reactive oxygen species, constitutive expression of SA-and ET/JA-responsive defence genes, and enhanced resistance to virulent bacterial and oomycete pathogens. Epistasis analyses of hrl1 with npr1, etr1, coi1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
123
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 87 publications
5
123
1
1
Order By: Relevance
“…(3) The AtrbohD mutant produces significantly more ET than the wild type even 24 h after the inoculation. (4) Lesion-free leaves of the hrl1 lesion-mimic mutant exhibit higher transcriptional rbohD induction than leaves actually displaying lesions (Devadas et al, 2002). (5) Most interestingly, as has been pointed out in two recent papers, pathogen-or host-associated molecular pattern elicitors such as flagellin (flg22) or oligogalacturonides do induce a rapid, transient, RBOHDdependent oxidative burst in Arabidopsis leaves detected by chemiluminescence or xylenol orange methods (Zhang et al, 2007;Galletti et al, 2008).…”
Section: Rbohd Interplays With Sa and Et In The Regulation Of Cell Deathmentioning
confidence: 94%
See 3 more Smart Citations
“…(3) The AtrbohD mutant produces significantly more ET than the wild type even 24 h after the inoculation. (4) Lesion-free leaves of the hrl1 lesion-mimic mutant exhibit higher transcriptional rbohD induction than leaves actually displaying lesions (Devadas et al, 2002). (5) Most interestingly, as has been pointed out in two recent papers, pathogen-or host-associated molecular pattern elicitors such as flagellin (flg22) or oligogalacturonides do induce a rapid, transient, RBOHDdependent oxidative burst in Arabidopsis leaves detected by chemiluminescence or xylenol orange methods (Zhang et al, 2007;Galletti et al, 2008).…”
Section: Rbohd Interplays With Sa and Et In The Regulation Of Cell Deathmentioning
confidence: 94%
“…Veinal necrosis and preceding accumulation of H 2 O 2 in turnip mosaic virus-infected Landsberg erecta Arabidopsis plants were dependent on the increased formation of SA and ET . SA and ET are also necessary for constitutive transcriptional activation of the rbohD gene in two different Arabidopsis lesion-mimic mutants (Devadas et al, 2002;Bouchez et al, 2007). Torres et al (2005) reported dramatically enhanced cell death in the lsd1 AtrbohD double mutant as a result of SA or BTH treatment in comparison with SA-or BTH-treated lsd1 or AtrbohD single mutant.…”
Section: Rbohd Interplays With Sa and Et In The Regulation Of Cell Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, mutant phenotypes indicate that PR1 expression is induced by SA and inhibited by JA (Turner et al, 2002). In the hypersensitive response-like lesions1 mutant, induction of PR1 expression requires both SA and ET, and induction of PDF1.2 expression requires all three hormones SA, ET, and JA (Devadas et al, 2002), indicating further levels of complexity in hormone interactions. Hence, it is likely that the timing, location, and levels of the various hormones determine the interaction (antagonistic or synergistic) and output responses.…”
Section: Introductionmentioning
confidence: 99%